(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To determine prospectively whether there is any relationship between a number of clinical factors and the degree of neuropathy of the optic nerve (ON) following intravitreal interventions in proliferative diabetic retinopathy (PDR). Materials and Methods: One hundred and five patients (105 eyes) with good anatomic results after undergoing vitrectomy were followed up and underwent visual evoked potential (VEP) testing at 2 months and 12 months. Results: At 2 months, neuropathy of the ON was observed in 56.1% of cases. Additionally, in 20.5% of these eyes, it was profound and characterized by intensely pale optic nerve head (ONH). At 12 months, the degree of neuropathy of the ON did not change. The functional activity of the visual system revealed by VEP tests (with 12-Hz flash, 1° and 0°15? checks) in study eyes was approximately 2-fold lower than normal values. Additionally, at both follow-up time points, the changes in VEP indices in eyes operated on for macular traction detachment were evidence of statistically significantly more profound degenerative processes in the nerve tissue than in eyes operated on for vitreous hemorrhage only. Conclusions: Progressive proliferative diabetic retinopathy is accompanied by a progressive neurodegenerative process in the retina and in the optic nerve, resulting in the development of a profound neuropathy of the optic nerve. The findings advocate the need for intensive neuroprotective therapy as well for as early as possible intravitreal intervention in this category of patients.